2022
DOI: 10.1186/s41687-021-00409-8
|View full text |Cite
|
Sign up to set email alerts
|

The endometriosis daily diary: qualitative research to explore the patient experience of endometriosis and inform the development of a patient-reported outcome (PRO) for endometriosis-related pain

Abstract: Purpose Endometriosis is a chronic disorder of the female reproductive system characterized by debilitating symptoms, particularly endometriosis-related pain (ERP). Patient-reported outcome (PRO) measures of symptoms and impacts are required to assess disease severity in ERP clinical studies and clinical practice. A content-valid instrument was developed by modifying the Dysmenorrhea Daily Diary (DysDD) to form the Endometriosis Daily Diary (EDD), an electronic PRO administered via handheld dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Prior qualitative research studies using concept-elicitation interviews in the US and Europe reported the most prevalent endometriosis symptoms as pelvic pain (or cramps), vaginal bleeding, dyspareunia, dysmenorrhea, and NMPP. 9,15,16 Other endometriosis symptoms identified in the present study, such as bloating, back pain, nausea, abdominal pain, fatigue, headaches, gastrointestinal distress, and lengthy/irregular cycles, are concordant with endometriosis symptoms reported in the literature. 9,[15][16][17][18] Endometriosis burden arises not only from symptoms of the disease (eg pain) but also accumulatively from the consequences of these symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Prior qualitative research studies using concept-elicitation interviews in the US and Europe reported the most prevalent endometriosis symptoms as pelvic pain (or cramps), vaginal bleeding, dyspareunia, dysmenorrhea, and NMPP. 9,15,16 Other endometriosis symptoms identified in the present study, such as bloating, back pain, nausea, abdominal pain, fatigue, headaches, gastrointestinal distress, and lengthy/irregular cycles, are concordant with endometriosis symptoms reported in the literature. 9,[15][16][17][18] Endometriosis burden arises not only from symptoms of the disease (eg pain) but also accumulatively from the consequences of these symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…9,15,16 Other endometriosis symptoms identified in the present study, such as bloating, back pain, nausea, abdominal pain, fatigue, headaches, gastrointestinal distress, and lengthy/irregular cycles, are concordant with endometriosis symptoms reported in the literature. 9,[15][16][17][18] Endometriosis burden arises not only from symptoms of the disease (eg pain) but also accumulatively from the consequences of these symptoms. The impact of endometriosis symptoms on women's lives as reported in the present study were generally consistent with impacts reported in other qualitative research studies, and included impacts on daily activities, appearance, emotional functioning, financial impact, physical activity, sex-related impacts, sleep, social activities, and work/school-related impacts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations